Pengaruh Disiplin Kerja Dan Kompensasi Terhadap Kinerja Pegawai - Ani Mahyuni; Danny Ramdani (Jurnal Ilmiah Wahana Pendidikan, 2022)
This study aims to determine, explain, and analyze the effect of work discipline and compensation on the performance of the Tenga Teknik staff of the Telagasari Section of the Watergate Officer, Karawang Regency. This research uses descriptive and verification methods. The sample in this study were 104 respondents using non-probability sampling. Data analysis with the help of Microsoft Excel 2019 and SPSS version 26. The results of this study indicate that there is a significant simultaneous effect of work discipline and compensation on employee performance by 71.9% and 28.1% influenced by other variables not examined.